Strength and difficulties questionnaire: A tool as prerequisite to measure child's mental health problems attending dental clinics - Nagendran Jayavel Pandiyan; Amitha Hedge (Wolters Kluwer Medknow Publications, 2016)
Introduction: Child's behavior on dental visit depends on variables such as age, parental behavior, parental anxiety, medical/dental history, and dental procedures. Behavioral-screening questionnaire, such as the Strengths and Difficulties Questionnaire (SDQ), can be used to preassess the child's mental health status which further predicts child behavioral pattern in dental clinics. Aim: To measure emotional status among children of 3-14 years age group attending dental clinics. Methodology: A total of 176 parents of children aged 3-14 years were involved in this study. The child's emotional and behavioral statuses were assessed using SDQ. Results: On analyzing the SDQ data, it was found that 80% of children came under the abnormal category whereas only 8% of children were found to be in normal category. Twelve percent of children came under borderline category. On the individual behavioral subsets scores, 13% were rated as abnormal on emotional subset, 40% on conduct problems, 12% on hyperactivity, and 29% on peer problems subset. Conclusion: Findings of this study suggest that incorporating tools to identify the current emotional state would give a clue and allow the dentist to develop a behavior guidance plan to accomplish the necessary oral health care. However, the results are preliminary; studies with larger sample should be done to validate the results among diverse populations.